NiO / MoS2 / rGO material as well as preparation method and application thereof
By preparing NiO/MoS2/rGO material and modifying the glassy carbon electrode to construct an electrochemical sensor, the problem of difficult efficient detection of methyl parathion in the existing technology was solved, and sensitive, stable and anti-interference detection effects were achieved.
Patent Information
- Application Number
- CN202510865933.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-09-23
AI Technical Summary
Existing technologies have difficulty in efficiently detecting methyl parathion (MP), especially when not relying on biological enzymes, and there are problems with detection sensitivity and selectivity.
NiO/MoS2/rGO materials were prepared and modified on the surface of glassy carbon electrodes to construct electrochemical sensors. The materials were prepared by hydrothermal method and other methods. By introducing NiO/MoS2/rGO materials, sensors were constructed. The key parameters of the reaction process were optimized by hydrothermal method and other methods. The materials formed achieved the detection performance of MP.
It realizes sensitive detection of MP and efficient detection of MP, and has good stability and anti-interference performance.
Smart Images

Figure CN120681795A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material synthesis and preparation of electrochemical sensors, and more particularly to a NiO / MoS2 / rGO material and a preparation method and application thereof. Background Art
[0002] Organophosphorus pesticides (OPs) are widely used in agriculture because they can effectively increase crop yields and ensure the quality of agricultural products. However, OPs can gradually accumulate through ecosystems and food chains, and even trace amounts of residues may pose a threat to food and environmental safety. Methyl parathion (MP), once widely used to control pests in various vegetables and fruits, is a typical OP pesticide. Due to the strong electron pull of the nitro substituents on its aromatic skeleton, its biodegradability is very poor. Therefore, many countries have banned the use of MP. Despite this, MP still remains in agricultural products such as fruits and vegetables and in the environment. Therefore, it is important to develop sensitive and efficient sensors to detect MP. Summary of the Invention
[0003] In view of this, the present invention prepares a composite material based on molybdenum disulfide (MoS2) and constructs an electrochemical sensor for detecting MP, thereby achieving sensitive and efficient detection of MP.
[0004] To achieve the above object, the present invention adopts the following technical solutions:
[0005] First, the present invention provides a method for preparing NiO / MoS2 / rGO material, comprising the following steps:
[0006] Step 1: Preparation of MoS2 / rGO
[0007] Sodium molybdate and thiourea were evenly dispersed in deionized water, GO suspension was added, ultrasonically mixed and then placed in a stainless steel autoclave for hydrothermal reaction. After the reaction, the mixture was washed and vacuum-dried at 60°C for 24 hours to obtain MoS2 / rGO composite material.
[0008] Step 2: Preparation of NiO / MoS2 / rGO
[0009] The MoS2 / rGO and NiO prepared in step 1 were mixed in a certain proportion and added into deionized water, ultrasonically dispersed for 90 minutes, and dried at 80°C to obtain a NiO / MoS2 / rGO composite material.
[0010] Preferably, in step 1, the molar ratio of sodium molybdate to thiourea is 1:5, the hydrothermal reaction temperature is 200° C., and the reaction time is 20 h.
[0011] Preferably, in step 2, the molar ratio of MoS2 / rGO to NiO is 1:0.4.
[0012] The present invention also provides a NiO / MoS2 / rGO material prepared by the method described in the above technical solution.
[0013] The present invention also provides a NiO / MoS2 / rGO material prepared by the method described in the above technical solution or the use of the NiO / MoS2 / rGO material described in the above technical solution in the preparation of an electrochemical sensor for detecting methyl parathion.
[0014] The present invention also provides a preparation method for the electrochemical sensor for detecting methyl parathion, comprising the following steps:
[0015] (1) NiO / MoS2 / rGO material was loaded on the GCE surface as a working electrode;
[0016] (2) placing the working electrode, counter electrode, and reference electrode prepared in step (1) in a three-electrode electrolytic cell, adding an electrolyte, and forming an electrochemical sensor for detecting methyl parathion.
[0017] Preferably, the specific loading process of step (1) is:
[0018] NiO / MoS2 / rGO was dispersed in DMF to prepare a 1 mg / mL dispersion, and a trace amount of Nafion solution containing 0.5% of the dispersion weight was added. Ultrasonication was performed for 40 minutes to obtain a uniform suspension. Then, 6 μL of the obtained suspension was dropwise applied to the GCE surface and dried in a 60°C air drying oven to obtain a NiO / MoS2 / rGO / GCE modified electrode, which was the working electrode.
[0019] Preferably, the counter electrode is a platinum electrode, and the reference electrode is an Ag / AgCl reference electrode.
[0020] Preferably, the electrolyte is 0.1 mol / L PBS, pH=7.3.
[0021] The present invention also provides an application of an electrochemical sensor for detecting methyl parathion prepared by the method described in the above technical solution in the detection of methyl parathion, wherein the detection concentration of the methyl parathion is 0.005-10 μg / mL, the enrichment potential is -0.4 V, and the enrichment time is 4 minutes.
[0022] It can be seen from the above technical solution that compared with the prior art, the present invention discloses a NiO / MoS2 / rGO material and its preparation method and application, which has the following beneficial effects:
[0023] The present invention successfully synthesizes MoS2 by a hydrothermal method and optimizes the key parameters of the reaction process, effectively improving its electrochemical detection performance for MP; the MoS2 / rGO composite material significantly improves the electrochemical detection performance for MP due to its good conductivity and interface structure; the present invention constructs a NiO / MoS2 / rGO ternary composite material by introducing NiO, and modifies it on the surface of a glassy carbon electrode (GCE) to construct a new electrochemical sensing platform. The sensing platform constructed by the present invention realizes efficient recognition and response to MP through the electron transfer behavior induced by the target molecules on the electrode surface. Without relying on biological enzymes, the system exhibits excellent stability and environmental adaptability. Comprehensive performance analysis shows that NiO / MoS2 / rGO / GCE not only has rapid, sensitive and highly selective detection capabilities, but also has good anti-interference properties and adaptability to actual samples, showing broad application prospects and promotion value. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0025] Figure 1 The effect of the molar ratio of sodium molybdate to thiourea on the detection of MP, where (a) is the DPV curve; (b) is the effect of the molar ratio of sodium molybdate to thiourea on the peak value of the response current;
[0026] Figure 2 The effect of hydrothermal temperature on the detection of MP, where (a) is the DPV curve; (b) is the effect of hydrothermal temperature on the peak value of the response current;
[0027] Figure 3 The effect of hydrothermal time on the detection of MP, where (a) is the DPV curve; (b) is the effect of hydrothermal time on the peak value of the response current;
[0028] Figure 4 The effect of MoS2 / rGO / GCE on MP peak current at different pH;
[0029] Figure 5 The effect of different GO addition amounts on MP peak current of MoS2 / rGO / GCE;
[0030] Figure 6 is the effect of enrichment potential on MP peak current;
[0031] Figure 7 is the effect of enrichment time on MP peak current;
[0032] Figure 8 SEM image of NiO / MoS2 / rGO;
[0033] Figure 9 EDS spectrum of NiO / MoS2 / rGO;
[0034] Figure 10 XRD patterns of MoS2, MoS2 / rGO, and NiO / MoS2 / rGO;
[0035] Figure 11 The full XPS spectra of MoS2 / rGO and NiO / MoS2 / rGO;
[0036] Figure 12 CV diagrams of GCE, MoS2 / GCE, MoS2 / rGO / GCE, and NiO / MoS2 / rGO / GCE;
[0037] Figure 13 Nyquist plots of GCE, MoS2 / GCE, MoS2 / rGO / GCE, and NiO / MoS2 / rGO / GCE;
[0038] Figure 14 CV graphs of MP on (a) GCE; (b) MoS2 / GCE; (c) MoS2 / rGO / GCE; (d) NiO / MoS2 / rGO / GCE;
[0039] Figure 15 (a) CV curves of NiO / MoS2 / rGO / GCE under different scan rate conditions (4 μg / mL MP 0.1 M PBS pH = 7); (b) corresponding standard curves;
[0040] Figure 16 Optimization of the ratio of MoS2 / rGO to NiO;
[0041] Figure 17 The effect of NiO / MoS2 / rGO loading on MP peak current;
[0042] Figure 18 (a) DPV diagram of NiO / MoS2 / rGO / GCE in PBS solutions containing different concentrations of MP; (b) linear fitting between reduction peak current and MP concentration;
[0043] Figure 19 (a) Reproducibility and (b) stability of NiO / MoS2 / rGO / GCE;
[0044] Figure 20This is the selectivity experiment of NiO / MoS2 / rGO / GCE for MP. DETAILED DESCRIPTION
[0045] The following will clearly and completely describe the technical solutions of the present invention in conjunction with the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts shall fall within the scope of protection of the present invention.
[0046] Example 1
[0047] Preparation of NiO / MoS2 / rGO:
[0048] Preparation of MoS2 / rGO composite materials:
[0049] 0.6 g of sodium molybdate and 1.1 g of thiourea were added to 20 mL of deionized water and stirred continuously for 15 minutes to ensure uniform dissolution. Then, 20 mL of GO suspension was slowly added to the above solution and ultrasonically treated for 30 minutes to obtain a uniformly mixed solution. The mixed solution was transferred to a 50 mL polytetrafluoroethylene liner, placed in a stainless steel high-pressure reactor, and reacted in a 200°C forced air drying oven for 20 hours. After the reaction was completed, the obtained product was washed to remove impurities and vacuum dried at 60°C for 24 hours to finally obtain MoS2 / rGO composite material.
[0050] Preparation of NiO:
[0051] 0.6 g of nickel chloride hexahydrate and 0.9 g of anhydrous sodium acetate were added to 30 mL of ethylene glycol, along with an appropriate amount of polyethylene glycol. The resulting solution was stirred and ultrasonically treated until a uniform green solution was obtained. The solution was then transferred to a 50 mL polytetrafluoroethylene liner and placed in a stainless steel autoclave for reaction at 160°C. After the reaction, the supernatant was discarded, and the precipitate was washed three times and dried at 80°C for 12 h. The dried product was calcined in a muffle furnace at 400°C and treated in air for 3 h, ultimately yielding a gray-green product.
[0052] Preparation of NiO / MoS2 / rGO:
[0053] The prepared MoS2 / rGO and NiO were mixed in a certain proportion and added into deionized water, which was ultrasonically dispersed for 90 min and dried at 80 °C to obtain NiO / MoS2 / rGO composite material.
[0054] Experimental Example 1
[0055] Process optimization of MoS2:
[0056] The preparation process of MoS2 is synthesized by hydrothermal method:
[0057] 0.6g of sodium molybdate was added to a beaker containing 40mL of deionized water and stirred at room temperature for 15 minutes. Subsequently, 0.44g, 0.67g, 0.89g, 1.11g, and 1.33g of thiourea were added to the solution, respectively, to achieve a sodium molybdate:thiourea molar ratio of 1:2, 1:3, 1:4, 1:5, and 1:6. The mixed solution, after ultrasonic treatment for 30 minutes, was poured into a 50ml polytetrafluoroethylene-lined container and reacted in a forced-air drying oven at 200°C for 20 hours. After the reaction, the mixture was washed with deionized water and then with anhydrous ethanol, repeated three times, and then vacuum-dried at 60°C for 2 hours to obtain MoS2.
[0058] Hydrothermal temperature optimization: Under the conditions of a sodium molybdate to thiourea molar ratio of 1:4 and a reaction time of 20 h, the reaction temperatures were set to 180°C, 190°C, 200°C, 210°C, and 220°C for experiments;
[0059] Optimization of hydrothermal time: Under the conditions of a molar ratio of sodium molybdate to thiourea of 1:4 and a reaction temperature of 200°C, the reaction time was set to 16 h, 18 h, 20 h, 22 h, and 24 h for experiments.
[0060] A MoS2 / GCE electrochemical sensor was constructed, and the effects of factors such as the sulfur-molybdenum ratio, hydrothermal temperature, and hydrothermal time on the electrochemical response performance of the sensor were systematically explored to determine the optimal preparation conditions for MoS2. Specifically, a three-electrode system was used as the detection platform for the electrochemical sensor, in which a glassy carbon electrode (MoS2 modified by drop coating) was used as the working electrode, an Ag / AgCl electrode was used as the reference electrode, and a platinum electrode was used as the counter electrode. Using the differential voltammetric pulse method (DPV), the potential range was set to -0.2-0.3V, the amplitude was 0.05V, and the pulse period was 0.2s. In the detection system with an electrode drop coating volume of 10μL, a buffer solution pH of 6, and an MP concentration of 20μg / mL, the optimal conditions for preparing MoS2 were determined by comparing the magnitude of the response current when MoS2 prepared under different conditions detected MP. The results are shown in the figure. Figure 1-3 As shown, Figure 1-3 The results showed that the optimal molar ratio of sodium molybdate to thiourea was 1:5, and the optimal conditions were hydrothermal temperature of 200 °C and hydrothermal time of 20 h.
[0061] Orthogonal optimization of MoS2 preparation process:
[0062] Based on the single-factor experimental results obtained for the sodium molybdate to thiourea molar ratio, hydrothermal temperature, and hydrothermal time, a three-factor, three-level orthogonal optimization experiment was conducted using a four-factor, three-level orthogonal table. The orthogonal experiments were conducted with sodium molybdate to thiourea molar ratios of 1:3, 1:4, and 1:5, hydrothermal temperatures of 190°C, 200°C, and 210°C, and hydrothermal times of 8 hours, 20 hours, and 22 hours. The orthogonal experimental table is shown in Table 1.
[0063] Table 1 Orthogonal test factor level table
[0064]
[0065] Based on the orthogonal test data, variance analysis was used to test the significance of the influencing factors. The orthogonal test results and variance analysis of each factor on the MP detection effect are shown in Table 2-3.
[0066] Table 2 Orthogonal experimental design and results
[0067]
[0068]
[0069] Table 3 Analysis of variance of orthogonal experiment
[0070]
[0071] Table 2 shows that the optimal process conditions for preparing MoS2 are A2B2C2, namely a sodium molybdate to thiourea molar ratio of 1:5, a hydrothermal temperature of 200°C, and a hydrothermal time of 20 hours. The variance analysis results in Table 3 show that the sodium molybdate to thiourea molar ratio and the hydrothermal temperature have the most significant effects on the MP response current of MoS2, while the sodium molybdate to thiourea molar ratio and the hydrothermal time have a more significant impact.
[0072] Experimental Example 2
[0073] Study on the detection performance of MoS2 / rGO / GCE for methyl parathion
[0074] Preparation of the MoS2 / rGO / GCE electrode: MoS2 / rGO was dispersed in DMF to a 1 mg / mL dispersion. A trace amount of Nafion solution (0.5 wt%) was added and sonicated for 40 minutes to obtain a uniform suspension. A 12 μL droplet of the resulting suspension was applied to the surface of a glassy carbon electrode and dried in a forced-air drying oven at 60°C to obtain the MoS2 / rGO / GCE-modified electrode.
[0075] In order to improve the detection performance of MoS2 / rGO / GCE sensor for MP, the detection conditions of MP were optimized by DPV method, mainly including the optimization of electrolyte solution pH, GO addition ratio, enrichment time and enrichment potential.
[0076] Optimization of pH: The effect of electrolytes with different pH values on the MP response current on MoS2 / rGO / GCE is shown in Figure 2. Figure 4 The results show that when the electrolyte pH is between 5.4 and 7.2, the MP reduction peak current increases with increasing pH. When the pH is between 7.2 and 8.4, the MP reduction peak current decreases with increasing pH. This may be because MP degrades in an alkaline environment. Therefore, pH 7.3 was selected as the optimal pH.
[0077] Optimization of GO addition: By changing the GO addition amount (10 mg, 15 mg, 20 mg, 25 mg, 30 mg, the mass ratio of MoS2 to GO is 37:1; 25:1; 19:1; 15:1; 12:1 respectively), the effect of MoS2 / rGO / GCE at different GO addition amounts on the MP peak current was investigated. The results are shown in Figure 5. Figure 5 As shown in the figure, with the increase of GO doping amount, the peak current of MP shows a trend of first increasing and then decreasing, and reaches the maximum value when the GO addition amount is 20 mg. Therefore, the GO addition amount of 20 mg (mass ratio of MoS2 to GO is 19:1) is selected.
[0078] Optimization of accumulation time and accumulation potential: Changes in MP peak current at different accumulation potentials are as follows: Figure 6 As shown in the figure, as the enrichment potential increases from -0.6 V to -0.4 V, the peak current of MP gradually increases and reaches its highest value at -0.4 V. As the enrichment potential continues to increase, the peak current of MP begins to decline. Therefore, -0.4 V is selected as the optimal enrichment potential.
[0079] like Figure 7 As shown in the figure, within the enrichment time range of 1-4 minutes, the peak current of MP gradually increased with the extension of the enrichment time. When the enrichment time exceeded 4 minutes, the peak current of MP did not increase significantly, so 4 minutes was selected as the optimal enrichment time.
[0080] Experimental Example 3
[0081] Study on the detection performance of NiO / MoS2 / rGO / GCE for methyl parathion
[0082] Preparation of the NiO / MoS2 / rGO / GCE electrode: NiO / MoS2 / rGO was dispersed in DMF to a 1 mg / mL dispersion. A trace amount of Nafion solution (0.5 wt%) was added and sonicated for 40 minutes to obtain a uniform suspension. A 6 μL droplet of the resulting suspension was applied to the surface of a glassy carbon electrode and dried in a forced-air drying oven at 60°C to obtain the NiO / MoS2 / rGO / GCE modified electrode.
[0083] Figure 8 The SEM images of NiO / MoS2 / rGO at different scanning magnifications are shown in Figure 2. Figure 8 As shown in Figure 3, NiO nanoparticles are evenly distributed on the surface of MoS2 / rGO sheets and between the pores, forming a granular covering structure, which further optimizes the morphology of sheet stacking.
[0084] Figure 9 This is the EDS energy spectrum of NiO / MoS2 / rGO. It can be seen from the figure that the strong peaks correspond to the Mo, S, C, Ni, and O elements in NiO / MoS2 / rGO, indicating that the prepared NiO / MoS2 / rGO is relatively pure.
[0085] Figure 10 The XRD patterns of MoS2, MoS2 / rGO, and NiO / MoS2 / rGO show that NiO has been successfully incorporated into the MoS2 / rGO composite, with a cubic crystal structure. Furthermore, the intensity of the characteristic peaks of MoS2 can be observed to be enhanced, indicating that the quality and crystal alignment of MoS2 in the composite have been improved, leading to enhanced electrochemical activity.
[0086] Figure 11 This is the full XPS spectrum of MoS2 / rGO and NiO / MoS2 / rGO. It can be observed from the figure that the MoS2 / rGO sample mainly contains Mo, S, C and O elements, and the NiO / MoS2 / rGO sample mainly contains Ni, Mo, S, C and O elements, indicating the successful introduction of NiO.
[0087] By CV method and EIS method, 5mmol / LK3[FeCN6] + The electrochemical performances of GCE, MoS2 / GCE, MoS2 / rGO, and NiO / MoS2 / rGO / GCE were evaluated in 0.1 mol / L KCl solution. Figure 12-13 As shown, Figure 12 The results indicate that the introduction of NiO may have a synergistic effect with MoS2 and rGO, further enhancing the redox reaction rate of the electrode. Compared with MoS2 / rGO, the NiO / MoS2 / rGO nanocomposite increases the number of active sites on the electrode surface and optimizes the electron transport pathway, ultimately improving electrode performance. Figure 13 This indicates that the diffusion impedance of NiO / MoS2 / rGO / GCE is relatively low, further proving that the composite material is conducive to the rapid diffusion and transport of ions.
[0088] The electrochemical behavior of MP on NiO / MoS2 / rGO / GCE and other control electrodes was studied by CV method in 0.1 mol / L PBS (pH = 7) solution with MP concentration of 4 μg / ml. Figure 14 As shown, MP has a larger response current on NiO / MoS2 / rGO / GCE.
[0089] Figure 15 The CV response of the NiO / MoS2 / rGO / GCE electrode in detecting MP at different scan rates is shown. By changing the scan rate (50-350mV / s), it can be observed that the redox peak current of the electrode increases with the scan rate. The scan rate (v) is fitted with the irreversible reduction peak current (Ipc) to obtain the following equation:
[0090] I pc =-0.325v+6.872(R 2 =0.984)
[0091] Among them, I pc represents the irreversible reduction peak current, and v represents the scan rate. From the above equation, we can see that I pc It is linearly related to v. According to the Laviron theory, the electrocatalytic reaction of MP on MoS2 / rGO / GCE is a typical adsorption-controlled process.
[0092] By changing the ratio of MoS2 / rGO to NiO (1:0.2, 1:0.3, 1:0.4, 1:0.5, 1:0.6), the effect of NiO / MoS2 / rGO / GCE on the MP peak current at different MoS2 / rGO to NiO ratios was investigated. Figure 16 As shown in the figure, when the ratio of MoS2 / rGO to NiO is 1:0.4, the current response reaches the maximum value, indicating that the synergistic effect between MoS2 / rGO and NiO is most significant, and the active sites and conductivity of the electrode surface are optimally balanced, thereby effectively improving the electrochemical response to the target molecules. Therefore, the ratio of MoS2 / rGO to NiO is selected to be 1:0.4.
[0093] The effect of the loading amount of NiO / MoS2 / rGO on the GCE electrode on the electrochemical response of MP was studied. The magnitude of the MP response current of NiO / MoS2 / rGO materials with loading amounts of 2, 4, 6, 8 and 10 μL on GCE was tested respectively. The experimental results are shown in the figure. Figure 17As shown in Figure 3, the peak current of MP gradually increases with the increase of NiO / MoS2 / rGO loading amount, and reaches the maximum value when the loading amount is 6 μL. Therefore, the optimal loading amount of NiO / MoS2 / rGO is selected as 6 μL.
[0094] DPV detection of MP by NiO / MoS2 / rGO / GCE
[0095] The DPV test results of NiO / MoS2 / rGO / GCE are as follows Figure 18 As shown in (a), the MP concentration range is 0.005-10μg / mL, and the electrolyte is 0.1mol / LPBS (pH=7.3) solution. It can be seen that with the increase of MP concentration, the reduction peak current gradually increases, indicating that NiO / MoS2 / rGO / GCE has good detection performance. Figure 18 (b) It can be seen that there are two linear relationships between the reduction peak current and the MP concentration. When the MP concentration is 0.005-0.5 μg / mL, the linear equation is: I pc (μA)=-25.378C MP -4.269(R 2 =0.993), when the MP concentration is 0.5-10 μg / mL, the linear equation is: pc (μA)=
[0096] -3.733C MP -16.314(R 2 =0.994). According to IUPAC standard method (LOD=3S b / K,S b The limit of detection (LOD) of NiO / MoS2 / rGO / GCE for MP was 1.3 ng / mL (S / N=3).
[0097] Reproducibility, stability and anti-interference of NiO / MoS2 / rGO / GCE:
[0098] Reproducibility and stability experiments:
[0099] DPV detection was performed using 6 NiO / MoS2 / rGO / GCE modified electrodes in a PBS solution with a MP concentration of 4 μg / mL. Figure 19 As shown in (a), the reduction peak current values of the six modified electrodes varied slightly, with an RSD of 3.6%. Six replicates of one electrode in a PBS solution with a MP concentration of 4 μg / mL yielded a RSD of 4.2%. This demonstrates the excellent reproducibility of the prepared NiO / MoS2 / rGO / GCE.
[0100] The prepared NiO / MoS2 / rGO / GCE was stored in a refrigerator at 4 °C and subjected to DPV tests at different time periods. The MP concentration remained at 4 μg / mL. Figure 19 (b) shows the changes in the response current after different storage times. As the storage time increases, the response current of NiO / MoS2 / rGO / GCE to MP slowly decreases. On the 18th day, the response current still remains at 85% of the initial current, indicating that the prepared NiO / MoS2 / rGO / GCE has excellent stability.
[0101] Anti-interference test:
[0102] Nitrobenzene compounds (nitrobenzene, nitrophenol) with similar structures to MP at 10 times the concentration; common organic interfering substances (ascorbic acid (AA), glucose (Glu)); inorganic oxygen-containing ion interfering substances (SO4 2- 、NO3 - PO4 3- ) and the same concentration of pesticide interferences (dimethoate (DIM), thiamethoxam (TMX)) were tested for anti-interference. The results are as follows Figure 20 As shown in the figure, it can be seen that various interferents have almost no effect on the peak current of MP, and the change amplitude of the peak current does not exceed 10% of the original current value, indicating that NiO / MoS2 / rGO / GCE also has good selectivity.
[0103] Experimental Example 4
[0104] The prepared NiO / MoS2 / rGO / GCE was used to test commercially available apples. The apples were cut into small pieces and squeezed into juice using a juicer. The juice was then mixed with 0.1 mol / L PBS (pH 7) to prepare a 50 mL sample solution. MP standard solutions at concentrations of 0.1, 0.5, 2, 4, and 6 mg / mL were added to the sample solution for actual sample analysis. The recovery rate was calculated according to the following formula:
[0105]
[0106] Under the optimal experimental conditions, the MP spike recovery was determined using the DPV method. Each sample was measured in triplicate, and the results are shown in Table 4. As can be seen from the table, the spike recovery of NiO / MoS2 / rGO / GCE for actual samples ranged from 97.7% to 108.8%, with relative standard deviations (RSDs) of 2.7% to 5.2%, indicating that the NiO / MoS2 / rGO / GCE sensor has good accuracy and good prospects for practical applications.
[0107] Table 4 MP determination in samples
[0108]
[0109]
[0110] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same and similar parts between the various embodiments can be referred to each other. The above description of the disclosed embodiments enables professionals and technicians in this field to implement or use the present invention. Various modifications to these embodiments will be apparent to professionals and technicians in this field, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but will conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing NiO / MoS2 / rGO material, characterized in that: The following steps are involved: Step 1: Preparation of MoS2 / rGO Sodium molybdate and thiourea were evenly dispersed in deionized water, GO suspension was added, ultrasonically mixed and then placed in a stainless steel autoclave for hydrothermal reaction. After the reaction, the mixture was washed and vacuum-dried at 60°C for 24 hours to obtain MoS2 / rGO composite material. Step 2: Preparation of NiO / MoS2 / rGO The MoS2 / rGO and NiO prepared in step 1 were mixed in a certain proportion and added into deionized water, ultrasonically dispersed for 90 minutes, and dried at 80°C to obtain a NiO / MoS2 / rGO composite material.
2. The method for preparing a NiO / MoS2 / rGO material according to claim 1, characterized in that: In step 1, the molar ratio of sodium molybdate to thiourea is 1:5, the hydrothermal reaction temperature is 200° C., and the reaction time is 20 h.
3. The method for preparing a NiO / MoS2 / rGO material according to claim 1, characterized in that: The molar ratio of MoS2 / rGO and NiO in step 2 is 1:0.
4.
4. A NiO / MoS2 / rGO material prepared by the method according to any one of claims 1 to 3.
5. Use of the NiO / MoS2 / rGO material prepared by the method according to any one of claims 1 to 3 or the NiO / MoS2 / rGO material according to claim 4 in the preparation of an electrochemical sensor for detecting methyl parathion.
6. A preparation method for the electrochemical sensor for detecting methyl parathion according to claim 5, characterized in that: The following steps are involved: (1) NiO / MoS2 / rGO material was loaded on the GCE surface as a working electrode; (2) placing the working electrode, counter electrode, and reference electrode prepared in step (1) in a three-electrode electrolytic cell, adding an electrolyte, and forming an electrochemical sensor for detecting methyl parathion.
7. The preparation of an electrochemical sensor for detecting methyl parathion according to claim 6, characterized in that: The specific loading process of step (1) is as follows: NiO / MoS2 / rGO was dispersed in DMF to prepare a 1 mg / mL dispersion, and a trace amount of Nafion solution containing 0.5% of the dispersion weight was added. Ultrasonication was performed for 40 minutes to obtain a uniform suspension. Then, 6 μL of the obtained suspension was dropwise applied to the GCE surface and dried in a 60°C air drying oven to obtain a NiO / MoS2 / rGO / GCE modified electrode, which was the working electrode.
8. The preparation of an electrochemical sensor for detecting methyl parathion according to claim 6, characterized in that: The counter electrode is a platinum electrode, and the reference electrode is an Ag / AgCl reference electrode.
9. The preparation of an electrochemical sensor for detecting methyl parathion according to claim 6, characterized in that: The electrolyte is 0.1 mol / L PBS, pH=7.
3.
10. Use of an electrochemical sensor for detecting methyl parathion prepared by the method according to any one of claims 6 to 9 in detecting methyl parathion, characterized in that: The detection concentration of methyl parathion is 0.005-10 μg / mL, the enrichment potential is -0.4 V, and the enrichment time is 4 minutes.